Structure and regulation of the Escherichia coli ruv operon involved in DNA repair and recombination. - Shinagawa, H (1988)
The ruv gene of Escherichia coli, which is involved in DNA repair and recombination, was cloned on a plasmid vector. The DNA of the ruv region was sequenced; it had two open reading frames in tandem that could code for 22- and 37-kilodalton proteins. The proteins encoded by these open reading frames were identified by the maxicell method. The two genes were aligned in the same orientation and regulated by the SOS system, so the two genes probably constitute an operon. The distal one complemented the ruv mutations. Transcription of the operon was studied both in vivo and in vitro. Two transcription initiation sites were identified upstream of the coding frames, and the transcription from both sites was repressed by the LexA repressor. A DNA sequence that is homologous to the SOS box and bound by LexA protein was found in the regulatory region of the operon. The amino acid sequence of Ruv protein deduced from the DNA sequence shows a high degree of homology to the consensus sequence shared by ATP-binding proteins.